The contours of party patronage in Argentina - Scherlis Perel, Gerardo Ezequiel (2013)
Studies on the Argentine public administration have usually underlined the weakness of Argentine state bureaucracies. On the basis of these assertions, scholars have tended to equate the number of state jobs with cases of patronage. By doing so, they have neglected the crucial issue of the scope of appointments effectively controlled by political parties. This article applies an innovative empirical inquiry to measure the extent of party patronage, assessing where, how deeply, and to what extent parties reach into the Argentine federal state structures. While the results by and large confirm the widespread notion of the broad scope of political appointments in Argentina, they refute the conventional hypothesis of a state thoroughly colonized by parties. Overall, the results suggest that parties’ distribution of public jobs in the Argentine federal state is oriented less to mass-style patronage than to gaining effective and broad control over state institutions.